Influência da qualidade institucional sobre as margens do comércio exterior brasileiro por intensidades tecnológicas - Bechlin, André Ricardo (2022)
International trade has a recognized importance in improving the well-being of society and the economic growth of regions and countries. Greater participation in foreign trade should be driven by lower costs or differentiated products and supported by productivity improvements, which in turn are a result of the economic environment, institutions, and national policies. The search for a closer empirical approximation of the dynamics of the international trade pattern should be carried out based on imperfect markets and with greater attention to the role played by the domestic institutional environment. In this context, the objective of this study will be to analyze the influence of the quality of the domestic and foreign institutional environment on Brazilian foreign trade margins according to different levels of technological intensity, between 1999 and 2019. As a methodology, gravity models were estimated using panel data by means of the multiplicative form using the Pseudo Poisson Maximum Likelihood (PPML) estimator. The models were estimated having as dependent variables the intensive (exported value) and extensive (exported quantity) trade margins, categorized according to five different technology intensity groups. As independent variables, the basic variables of the gravity model, binary variables, and the values referring to the six institutional quality indices for Brazil and other 192 trade partner countries were used. The variables contiguity, GDP, and participation of the importing country as a member of the WTO had a positive influence on Brazilian export margins, while distance had a negative influence. When considering the institutional quality variables, there was a greater influence of external variables when compared to internal ones, since there was a greater number of variables linked to importing countries with statistically significant values, but with a negative sign, showing that improvements in the institutional quality of partner countries lead to a reduction in total exports.